Kalophrynus (Anura: Microhylidae), a new genus for India, with the description of a new species, Kalophrynus orangensis, from Assam state - Dutta, S.; Mohammad Firoz, Ahmed; Das, I. (Centre for Herpetology, Madras Crocodile Bank Trust, 2000)
The microhylid genus, Kalophrynus, is reported for the first time from India, and a new species, Kalophrynus orangensis is described from the Orang National Park, Assam in north-eastern India. K. orangensis is diagnosable from all other congeners in showing the following combination of characters: snout acute, projecting beyond mandible; parotid gland absent; head wider than long; an inverted ‘v’-shaped mark present on dorsum from tip of snout to the inguinal region; an ocellus present on inguinal region; fingers lacking webbing; toes with rudimentary webbing; a single subarticular tubercle on finger IV; inner outer metatarsal tubercles present; and SVL of adults constituting the type series, 35.0-38.0 mm.